Do Accounting, Market, and Macroeconomic Factors Affect Financial Distress? Evidence in Indonesia - Muhammad Taufik; Clarita Valeria Sugianto (Universitas Airlangga, 2021)
This paper aims to investigate the effect of accounting, market, and macroeconomic factors on financial distress. The investigations were expanded by constructing seven research models to simulate all factors. The research sample includes companies listed on the IDX from 2016 to 2020 which produce 1.710 data. This paper finds that retained earnings (RETA) and earnings (EBITTA) as part of accounting factors have a role in weakening financial distress and can be consistently tested in several research models. Equity (MVE) as part of the market factor weakens financial distress and is consistently tested. Although solvency (SOLV) was described as the company's ability to maximize debt, it is not consistently tested in several research models. Finally, it was found that deflationary conditions caused financial distress which represented macroeconomic factors. This paper makes a practical contribution to companies and governments to evade financial distress